SENSATION FICTION - ANDREW MANGHAM (LONDON CAMBRIDGE UNIVERSITY PRESS, 2013)
This Companion highlights the energy, the impact and the inventiveness of the novels that were written in 'sensational' style, including the work of Mary Elizabeth Braddon, Mrs Henry Wood and Florence Marryat. It contains fifteen specially-commissioned essays and includes a chronology and a guide to further reading. Accessible yet rigorous, this Companion questions what influenced the shape and texture of the sensation novel, and what its repercussions were both in the nineteenth century and up to the present day
Keywords: English Novel-Criticism -- Sensationalism in Literature